Analisis Potensi dan Pengembangan Agrofrestri berbasis Kopi di Desa Colo Kecamatan Lamba Leda Timur Kabupaten Manggarai Timur - Agustinus Charles Muras; Maria M. E. Purnama; Fadlan Pramatana (Wana Lestari, 2023)
A SWOT analysis was conducted to obtain data regarding the potential and strategies related to the development of coffee-based agroforestry in Colol Village, East Manggarai Regency, based on information regarding internal factors (strengths and weaknesses) and external factors (opportunities and threats). This study aims to determine the potential for developing coffee-based agroforestry in supporting the economy of the community around the agro- tourism area in the village of Colol, East Lamba Leda District, East Manggarai Regency. The potential of coffee-based agroforestry in supporting the economy of the community around the agro-tourism area in Colol, East Lamba Leda District is a hydrological aspect and an economic aspect. Meanwhile, the suggested strategy that is appropriate for the development of coffee-based agroforestry is the SO (strength opportunity) strategy, which is a strategy for existing strengths by taking advantage of existing opportunities, with the availability of land and favorable geographical conditions that must be optimized for the development of coffee-based agroforestry, the demand for coffee continues to increase. increased, and support from the government for coffee-based agroforestry farmer businesses in Colol Village, East Lamba Leda District. This is very important because local government policies determine the direction of plantation development and development in the future to support the community's economy. Utilizing the experience and knowledge of farmers is very important in the development of coffee-based agroforestry. This is very supportive in the cultivation of coffee plants with agroforestry patterns as well as in their management and marketing.